You are not logged in.

- Topics: Active | Unanswered

Pages: **1**

**henrylee****Guest**

How do you solve this equation?

-(3/5)+(x/10)=-(1/5)-(x/5)

**ryos****Member**- Registered: 2005-08-04
- Posts: 394

Put the x's on one side and everything else on the other:

x/10 + 2x/10 = -1/5 + 3/5

Simplify:

3x/10 = 2/5

3x = 20/5 = 4

x = 4/3

The key is that to add or subtract fractions, you need a common denominator. Once you can combine all the fractions, it becomes simple to solve.

El que pega primero pega dos veces.

Offline

Pages: **1**